2023
DOI: 10.1371/journal.pgen.1010753
|View full text |Cite
|
Sign up to set email alerts
|

Taste and pheromonal inputs govern the regulation of time investment for mating by sexual experience in male Drosophila melanogaster

Abstract: Males have finite resources to spend on reproduction. Thus, males rely on a ‘time investment strategy’ to maximize their reproductive success. For example, male Drosophila melanogaster extends their mating duration when surrounded by conditions enriched with rivals. Here we report a different form of behavioral plasticity whereby male fruit flies exhibit a shortened duration of mating when they are sexually experienced; we refer to this plasticity as ‘shorter-mating-duration (SMD)’. SMD is a plastic behavior a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 100 publications
1
17
0
Order By: Relevance
“…We found that, after spending 2.5 hours mating ad libitum with females in a satiety assay (1 male with ∼15 virgin females 6,34 ; see Methods ), males become much more likely to terminate subsequent matings when challenged ( Figure 1A, B, Supplementary Figure 1B ). This manifestation of satiety lasts for at least a day ( Figure 1B ), holds across multiple threat modalities ( Figure 1C ), and, in agreement with previous reports 6,35 , does not alter the duration of unchallenged matings ( Supplementary Figure 1C ).…”
Section: Resultssupporting
confidence: 91%
“…We found that, after spending 2.5 hours mating ad libitum with females in a satiety assay (1 male with ∼15 virgin females 6,34 ; see Methods ), males become much more likely to terminate subsequent matings when challenged ( Figure 1A, B, Supplementary Figure 1B ). This manifestation of satiety lasts for at least a day ( Figure 1B ), holds across multiple threat modalities ( Figure 1C ), and, in agreement with previous reports 6,35 , does not alter the duration of unchallenged matings ( Supplementary Figure 1C ).…”
Section: Resultssupporting
confidence: 91%
“…Forty to fifty adults were used for climbing assay. Statistical comparisons were made between Figures 7, 8, and S9) (Lee et al, 2023). In short, "estimation statistics" is a simple framework that-while avoiding the pitfalls of significance testing-uses familiar statistical concepts: means, mean differences, and error bars.…”
Section: Discussionmentioning
confidence: 99%
“…Individual tests and significance are detailed in figure legends. Besides traditional t ‐test for statistical analysis, we added estimation statistics for all climbing assays and two group comparing graphs (Figures 7, 8, and S9) (Lee et al., 2023). In short, “estimation statistics” is a simple framework that—while avoiding the pitfalls of significance testing—uses familiar statistical concepts: means, mean differences, and error bars.…”
Section: Methodsmentioning
confidence: 99%
“…Single-cell RNA sequencing (scRNA-seq) data from the Drosophila melanogaster were obtained from the Fly Cell Atlas website (https://doi.org/10.1126/science.abk2432). (Li et al 2022) Statistical Tests Statistical analysis of mating duration assay was described previously (Kim et al 2012(Kim et al , 2013Lee et al 2023). More than 50 males (group and single) were used for mating duration assay.…”
Section: Immunostainingmentioning
confidence: 99%
“…This cognitive function is thought to be in uenced by both hemispheres of the brain, with each hemisphere contributing to different aspects of time perception (Polzella et al 1977; Mitrani 1984, 1985). Interval timing is a fundamental cognitive process that is conserved across a broad spectrum of biological diversity, ranging from humans to insects (Boisvert and Drosophila also exhibit interval timing behaviors, such as rival-induced prolonged mating duration (LMD) (Bretman et al 2009; Kim et al 2012Kim et al , 2013 and sexual experience-mediated shorter mating duration (SMD) (Lee et al 2023). These behaviors require the integration of sensory cues and the formation of long-term memory (LTM) (Kim et al 2012(Kim et al , 2016.…”
Section: Introductionmentioning
confidence: 99%